Lower area, less drag? The energy cost of an able body and shoulder amputee cyclist by CFD - Tatiana Sampaio; Jorge Estrela Morais; Daniel Almeida Marinho; Tiago Manuel Barbosa; António Miguel Monteiro; Pedro Forte (Desafio Singular, 2024)
In cycling, drag is the force that opposes the cyclist's motion and is caused by the cyclist's and their equipment's interaction with the air. The surface area of the cyclist and their equipment, such as the bike, helmet and body postures, have a substantial impact on how much drag they encounter. This study compared the energy cost an able-bodied and shoulder amputee cyclist through numerical simulations using computer fluid dynamics. According to the hypothesis, an able-bodied cyclist may use more energy at a given speed than an able-bodied cyclist. For this study, a professional male cyclist who weighs 65 kg and is 1.72 m tall took part. The estimated energy cost was lower in an shoulder amputee in comparison to the able-bodied cyclist. Significant statistical differences and relationships were found between the cyclists for the 11 selected speeds. Altogether, this study allows to conclude that, for the same conditions, an able-bodied cyclist deliver less energy cost in comparison to a shoulder amputee.